Implementasi Pancasila di Tahun Politik - Christo Sumurung Tua Sagala; Mirza Nasution (Jurnal Adhyasta Pemilu, 2022)
Pancasila as the ideology and philosophy of the nation and state becomes a unifier and guides the motivation of the nation to achieve the ideals of realizing a life that upholds divinity, human values, unity, democracy, and justice. Elections are a means of democracy which is also one of the ideals of the Pancasila and is not just a slogan but must be implemented to avoid divisions within the country. However, in the year of general election which is commonly called the political year, it is not uncommon for conflicts to occur between the people which even result in conflicts in society caused by differences in choices and opinions between one another. The purpose of this study is to determine the implementation of Pancasila values and the protection and enforcement of the law in the implementation of elections in Indonesia. The research was conducted with a normative-descriptive approach by examining secondary data sourced from laws and regulations, books, expert views, articles/writings and other sources of material then compiled systematically and then analyzed qualitatively by assessing the effectiveness of its application. From the results of the study, it can be concluded the implementation Pancasila of the democracy in Indonesia is still very minimal, with the rise of identity politics issues in the implementation of elections which will have a bad impact on democracy in Indonesia to divide the sense of unity and diversity of the multiethnic Indonesian people, multicultural and multi-religious. In addition, law enforcement is also still less than optimal due to several factors such as imperfect regulations, the number of institutions involved in law enforcement and the short period of handling.